The aftermath of multiple trauma on a nation: unraveling Lebanon’s unique mental health struggle - Karam, Elie G.; El-Jamal, Mariam; Osman, Rayane; Toukan, Sana; Mouawad, Ghiwa Ishac; Al Barathie, Josleen (Frontiers in Psychiatry, 2025)
ObjectiveThis study examines the national prevalence of mental health disorders and their associated factors in Lebanon, specifically in the aftermath of the 2020 events, including the catastrophic events of Beirut blast and the concurrent financial meltdown amid the global pandemic.MethodsConducted between July and September 2022, the study interviewed a nationally representative sample of 1,000 Lebanese via telephone, using the Computer Assisted Telephone Interview (CATI) system. Gender-specific bivariate and multivariate models were generated for probable posttraumatic stress disorder (PTSD), depression, and anxiety.ResultsHigh rates of mental health disorders emerged — 47.8% screened positive for probable depression, 45.3% for probable anxiety, and 43.5% met the probable diagnosis for PTSD. Multivariate gender-specific analyses revealed no significant associations with governorate, employment status, or marital status, while the financial composite score consistently influenced all disorders.ConclusionLebanon faces a severe mental health crisis, evidenced by elevated rates of probable depression, anxiety, and PTSD. The universal impact of multiple traumas transcends typical determinants, emphasizing the need for nuanced interventions and targeted policy considerations.